Capacidades dinâmicas: a atuação dos elementos do strategizing, da aprendizagem e do isomorfismo no processo de desenvolvimento de produto - Melo, Germana Tavares de (2017)
Considering that product development is an example of dynamic capability, the advocated thesis argument consists in the understanding that the elements of strategizing (practice, praxis and practitioners), together with learning and isomorphic mechanisms present in the organizational field explain the process of how the development of dynamic capabilities occurs. In this sense, the aim of this research was to analyse how the elements of strategizing (practice, praxis and practitioners), together with learning and isomorphic mechanisms present in the organizational field, explain the product development process. Methodologically, it was used a qualitative approach and the method applied was narratives of practice, which were held in two companies working with product development: São Braz and ShoesShop. In order to collect the data it was used narrative interviews, non-participant observation and document analysis during the period between May 2015 and May 2016. Data were analysed using narrative analysis. The results showed that the learning processes (intuition, interpretation, integration and institutionalization), underlying the product development, are mediated by learning mechanisms (experience accumulation, knowledge articulation and codification of knowledge). The appropriated practices and institutionalized praxis by the organizations surveyed explain the product development process and are performed by practitioners. The role played by external practitioners, such as consultants, proved to be important, as because of their work, practices were adopted by organizations. Some practices that prevail in the organizational environment and that are institutionalized in society are incorporated by both São Braz and ShoesShop with a view to development products through coercion, mimesis and normativity, demonstrating that the isomorphism also explains the product development process in companies. It was concluded that the use of the strategy as practice approach associated with the performance of isomorphic mechanisms and learning explain the product development process and represent an advance in knowledge about the development of dynamic capabilities. Additionally, the identification of practice, praxis and practitioners in building routines gives greater robustness to the product development process, as companies come to know more clearly the most important elements in this process and therefore deserve more attention.